2017
DOI: 10.1021/acs.energyfuels.7b02098
|View full text |Cite
|
Sign up to set email alerts
|

Production of Liquefied Oil Palm Empty Fruit Bunch Based Polyols via Microwave Heating

Abstract: Optimization of microwave-assisted liquefaction of oil palm empty fruit bunch fiber (EFB) and cellulose (EFBC) in ethylene glycol (EG) was carried out to produce polyols. The liquefaction residues and hydroxyl numbers of the resultant polyols from respective sources were studied and compared. EFB produced a minimum residue of 3.22% at the optimal parameters of 160 °C and 15 min. Meanwhile, optimum liquefaction of EFBC produced 1.03% residue at 175 °C and 40 min. The maximum hydroxyl numbers of both EFB (749.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The liquefaction yield tended to be stable after the reaction time was >90 min. In the case of temperature ≥150 °C, the partial degradation of the crystalline cellulose occurred, as reported in previous literature [ 32 ]. Moreover, the liquefaction yield at each investigated temperature reached the maximum value at the reaction time of 120 min.…”
Section: Resultssupporting
confidence: 77%
“…The liquefaction yield tended to be stable after the reaction time was >90 min. In the case of temperature ≥150 °C, the partial degradation of the crystalline cellulose occurred, as reported in previous literature [ 32 ]. Moreover, the liquefaction yield at each investigated temperature reached the maximum value at the reaction time of 120 min.…”
Section: Resultssupporting
confidence: 77%
“…As for AlCl 3 , the yield increased from 28.81%-71.57%, with an increment of purity from 83.39%-92.89%. Basically, temperature plays a vital role in lignin extraction as it enhances the degradation of cell walls while the lignin and hemicellulose were decomposed and dissolved in the organic solvent (Amran et al, 2017;2019). The higher yield obtained was also due to the extensive lignin depolymerisation which led to higher lignin solubilisation in the organic solvent, especially with the presence of microwave irradiation (Monteil-Rivera et al, 2012).…”
Section: Effect Of Reaction Temperature and Catalyst On Yield Of Crudmentioning
confidence: 99%
“…In recent years, concerns over the continuous depletion of fossil resources as well as an increment in ecological awareness have drawn a remarkable interest to reduce the dependence on fossil resources as raw materials. Countless research have been conducted to overcome these issues and lignocellulosic biomass has been considered as the best candidate to replace or provide alternative to petroleum-based materials (Amran et al, 2017). This reason is not only for its sustainability but the content of cellulose, lignin, and hemicellulose in the biomass provide various functionalities and structures that can be tailored into desired applications.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass Type. Since Krzan et al first applied microwave energy to liquefaction [19,20], a variety of biomass types including sweetgum sawdust [8]; agricultural residues including bagasse, corn stover, rice straw, wheat straw, cotton stalk, and corncobs [24][25][26]; organosolv lignin of olive tree prunings [27]; Sargassum polycystum C. Agardh [28]; microalgae [29]; Ulva prolifera [30]; wheat straw alkali lignin International Journal of Polymer Science [31]; sugar beet pulp [32]; peony oil palm empty fruit bunch fiber [16]; oil palm empty fruit bunch cellulose [33]; poplar; Chinese fir; bamboo; hemp xyloid stem [22]; mixed softwood pellets [34]; banana pseudostem [35]; coconut fiber [36]; and grapefruit [37] have been studied as raw materials for microwave-assisted liquefaction for the production of renewable chemical platforms and/or biobased materials. The chemical composition (cellulose, hemicellulose, lignin, and ash) and microstructure of the lignocellulose feedstocks greatly differed with each other, which may influence their liquefaction behaviors under microwave heating.…”
Section: Lignocellulosic Biomass Sources Formentioning
confidence: 99%
“…The significant microwave liquefaction factor is temperature, and the reason may be that temperature enhances and attacks solvents and catalysts onto glycosidic linkages resulting in the decomposition of cellulose into small molecules [69]. The optimum liquefaction temperature and time for oil empty fruit bunch fiber and oil palm empty fruit bunch fiber cellulose was 160°C with 15 min and 175°C with 40 min [33]. The research results on the liquefaction of coconut fiber indicated that the optimal reaction temperature was 160°C [36].…”
Section: Microwave Liquefaction Process Optimizationmentioning
confidence: 99%